Cellular effects of oral egg yolk immunoglobulin-based supplementation at birth on promoting growth and strengthening intestinal mucosal innate immunity in pre-weaned piglets - Lothong, Muttarin; Kayan, Autchara; Malison, Manmueang; Rakarcheep, Dran; Samritwatchasai, Theerawat; Thammacharoen, Sumpun; Deachapunya, Chatsri; Poonyachoti, Sutthasinee (Frontiers in Veterinary Science, 2025)
Low birth weight harms growth and immunity in suckling piglets. The effects of chicken egg yolk immunoglobulin (IgY)-based product, Globigen® Pig Doser (EW Nutrition GmbH, Visbek, Germany) (GPD), administered at birth on growth performance at weaning were investigated in normal (NBW) and low birth weight (LBW) piglets. The product comprises IgY antibodies against common enteric pathogens in newborn piglets, such as Escherichia spp., antibodies against common enteric pathogens in newborn piglets, such as Escherichia spp., as well as soybean oil, vitamins, and probiotics like Enterococcus faecium. The expression of mRNA and protein related to mucosal innate immunity was measured using real-time quantitative polymerase chain reaction (qPCR) and Western blot in 7-day-old piglets (n = 5 piglets). LBW (0.8–1.0 kg birth weight [BW]) and NBW (1.4–1.6 kg BW) piglets were randomly chosen from different sows. At 6 and 10 h after birth, 1.5 mg of IgY (NBW-IgY or LBW-IgY piglets; n = 32 piglets/group) was orally supplemented. GPD significantly increased the final BW and daily weight gain of NBW-IgY but not LBW-IgY piglets at 24 days after birth compared to the untreated group. The growth performance of LBW-IgY piglets was improved to match NBW piglets. The expressions of antimicrobial peptides, porcine β-defensin (PBD)4, pathogen recognition receptors, toll-like receptor (TLR)1, TLR2, TLR5, TLR6, TLR8, and TLR9, and cytokines IL-6 were enhanced in NBW-IgY. The upregulated expressions of PBD2 and PBD4 were observed in the jejunal mucosa of LBW-IgY piglets. GPD reversed the overexpression of neuropeptides substance P, calcitonin gene-related peptides, and cytokines interleukin 8 (IL-8) that underlie inflammation in the LBW group. The LBW group exhibited elevated expression of tight junction (TJ) barrier proteins, including claudin (CLDN)4, CLDN7, and ZO-1 in the colon, but these levels were reversed by GPD. Our findings indicated that oral GPD supplementation at birth can promote growth by modulating the intestinal barrier system and reducing the incidence of inflammation in pre-weanling piglets.